Studi Literatur: Penggunaan Obat Remdesivir dan Favipiravir dalam Terapi Covid-19 - Sri Lestari; Dewi Mayasari; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Coronavirus Disease 2019 (COVID-19) is a respiratory disease caused by the new coronavirus and is spreading rapidly throughout the world. Several studies were conducted to find these antiviral agents, one of which is Remdesivir and Favipiravir. This literature study aims to examine the use of Remdesivir and Favipiravir as therapy in COVID-19 patients with a literature study. The research method used is a literature review with an electronic database of indexed journals with a journal publication time limit for 2019-2020 using the appropriate keywords. From the 10 literature that has been reviewed, it shows that the use of Remdesivir and Favipiravir in the treatment of COVID-19 provides an improvement in the patient's health condition.